Implementasi Dana Desa dalam Meningkatkan Kesejahteraan Masyarakat Desa Berdasarkan Undang-Undang Nomor 6 Tahun 2014 Tentang Desa - Ilham Zitri; Rifaid Rifaid; Yudhi Lestanata (Universitas Pancasakti, 2020)
The Village Fund is one of the government policies that is prioritized to finance the development and empowerment of the community, the implementation of which is prioritized by using self-managed resources / local raw materials, and strived by absorbing more local workforce. This study aims to determine the use of village funds used in accordance with the program, the results of the use of village funds and community involvement in the Village of Poto Tano, District of Poto Tano, West Sumbawa Regency. The research approach used is descriptive qualitative. Using data collection techniques through interviews with informants who are considered to have the potential to provide information about the use of the Village Fund in the development of Poto Tano Village, Poto Tano Subdistrict, West Sumbawa Regency, also through observation and documentation of the results of the utilization of the Village Fund. The results showed that the Utilization of Village Funds in Improving the Welfare of Poto Tano Village, Poto Tano Subdistrict, West Sumbawa Regency, Based on Law Number 6 of 2014 concerning Villages could not be said to be effective. This can be proven by the number of Community Empowerment programs that are still far different from the number of Village Development programs that have been realized in accordance with the plan of the program set by the Village Government through the Musrenbangdes. Community involvement in the implementation of the use of village funds in Poto Tano Village also cannot be said to be good, where the community is still not fully included in the preparation up to the implementation of the programs that were set at the time of the Musrenbangdes. Keywords: Implementation, Village Funds, Public welfare.